Chaordic destination image formulation through gastronomy perspectives: evidence from Greece - Pappas, Nikolaos; Michopoulou, Eleni; Farmaki, Anna; Leivadiotaki, Emmanouela (My University, 2022)
Purpose: This study aims to evaluate the complex behaviour of tourists in terms of the formulation of destination image related to its gastronomy. Through the examination of gastronomic image, memorability of experiences and food personality traits such as neophobia and neophilia, this research investigates the chaordic (chaos versus order) systems and provides specific pathways that formulate the gastronomic destination image. Design/methodology/approach: Using fuzzy-set qualitative comparative analysis (fsQCA), this study examines the chaordic relations amongst memorable tourism experiences (MTEs), gastronomic neophobia and neophilia and gastronomic image upon the formulation of destination image. This study also includes two grouping variables (nationality [stratified], age). Findings: Three sufficient configurations were revealed that can lead to the formulation of destination image, explaining the attributional gastronomic decision-making of holidaymakers. These solutions concern: food personality traits, generated experience and gastronomic image. Research limitations/implications: In spite of the need for examining the complexity and the chaordic systems in the gastronomic domain, the lack of a sufficient number of studies using fsQCA hinders its full potential. The complete lack of gastronomic studies using this method highlights the necessity of its use for research in the respective field. Originality/value: This study explores the complexity of how food-related personality traits influence the attainment of MTEs and the formulation of gastronomic image and how the chaordic systems influence the overall image of a destination.
Keywords: Destination image; Food; Food and drink; Gastronomy; Memorable experiences; Personality traits; Tourism experiences